2017
DOI: 10.1159/000485079
|View full text |Cite
|
Sign up to set email alerts
|

Return to Work of Cancer Survivors

Abstract: Due to improving treatment options, the number of so-called long-term cancer survivors is steadily increasing. Current studies assume that more than 60% of adults survive their cancer. These patients have a variety of problems (chemotherapy-induced neuropathy, fatigue, etc.) that require very special care. In addition to somatic and psychological side effects of the cancer or its treatment, these patients also suffer from the financial and social consequences of the disease. Thus, for a long-term survivor of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 28 publications
0
36
0
2
Order By: Relevance
“…It furthermore is crucial that employers learn more about the effects of cancer and its treatment—as echoed by survivor participants in our study—as lack of knowledge can serve as a barrier to survivors' RTW (McKay, Knott, & Delfabbro, ; Stergiou‐Kita et al, ; Tiedtke, Dierckx De Casterle, Donceel, & Rijk, ). Similarly, improving communication between employees and frontline managers can foster trust in divulging sensitive information (Gudbergsson, Fosså, Lindbohm, & Dahl, ; Seifart & Schmielau, ). Prior studies indicate that certain elements of employee–employer communication facilitate workplace interaction, including communication that is respectful of survivors' values and preferences, elicits information about survivors' work limitations and required accommodations, and includes regular check‐ins to assess their well‐being (Dorland et al, ; Frazier et al, ; Tiedtke et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It furthermore is crucial that employers learn more about the effects of cancer and its treatment—as echoed by survivor participants in our study—as lack of knowledge can serve as a barrier to survivors' RTW (McKay, Knott, & Delfabbro, ; Stergiou‐Kita et al, ; Tiedtke, Dierckx De Casterle, Donceel, & Rijk, ). Similarly, improving communication between employees and frontline managers can foster trust in divulging sensitive information (Gudbergsson, Fosså, Lindbohm, & Dahl, ; Seifart & Schmielau, ). Prior studies indicate that certain elements of employee–employer communication facilitate workplace interaction, including communication that is respectful of survivors' values and preferences, elicits information about survivors' work limitations and required accommodations, and includes regular check‐ins to assess their well‐being (Dorland et al, ; Frazier et al, ; Tiedtke et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients in this study described a number of phenomena that have been described elsewhere including changes in established relationships, shifts in caregiver roles, disconnection from work, and alteration in physical appearance . This study connects these phenomena to engagement in the health care recipient domain through a framework of identity.…”
Section: Discussionmentioning
confidence: 79%
“…Almost a decade and a half later, we have seen a rapid increase in articles and reviews on cancer survivorship and work. These articles have shown that cancer survivors do indeed have a higher risk of unemployment or no return to work compared with healthy individuals [3,7]. Most of these studies have been limited to survivors of breast cancer, short-term work outcomes (up to 5 years) and North American or European populations [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…These articles have shown that cancer survivors do indeed have a higher risk of unemployment or no return to work compared with healthy individuals [3,7]. Most of these studies have been limited to survivors of breast cancer, short-term work outcomes (up to 5 years) and North American or European populations [3,7]. The most frequently studied long-term effects of cancer treatment affecting sustainable work participation include fatigue, physical problems, anxiety and depression [8].…”
Section: Introductionmentioning
confidence: 99%